Compact single-longitudinal mode microchip laser operating at 532 nm - Sotor, Jaroslaw; Dudzik, Grzegorz; Abramski, Krzysztof (Photonics Letters of Poland, 2014)
In this paper we present compact, single-longitudinally mode diode pumped microchip laser operating at 532 nm. The laser is based on a monolithic Nd:YVO4/YVO4/KTP laser resonator. It is fully integrated with specially designed driving electronics, power supply unit mechanical assembly, pumping unit, beam expander and can work as an independent device. Thanks to the monolithic resonator design and low noise driving electronics the laser is highly resistant to environmental hazards. The output power, passive frequency stability and linewidth were at the level of 55mW, 3•10-9 @ 1s mean time and 25kHz, respectively. Full Text: PDF References H. Yang, J. Deibel, S. Nyberg, K. Riles, "High-precision absolute distance and vibration measurement with frequency scanned interferometry", Appl. Opt. 44, 3937 (2005), CrossRef S.P. Perfetto, M. Roederer, "Increased immunofluorescence sensitivity using 532 nm laser excitation", Cytometry Part A 71A, 73 (2007). CrossRef A. Antonczak, P. Koziol, J. Sotor, P. Kaczmarek, K.M. Abramski, "Laser Doppler vibrometry with a single-frequency microchip green laser", Meas. Sci. Technol. 22, 115306 (2011). CrossRef C.L. Tang, H. Statz, G. deMars, "Spectral Output and Spiking Behavior of Solid?State Lasers", J. Appl. Phys. 34, 2289 (1963). CrossRef J.J. Zayhowski, "Limits imposed by spatial hole burning on the single-mode operation of standing-wave laser cavities", Opt. Lett. 15, 431 (1990), CrossRef J.J. Zayhowski, A. Mooradian, "Single-frequency microchip Nd lasers", Opt. Lett. 14, 24(1989), CrossRef T. Taira, A. Mukai, Y. Nozawa, T. Kobayashi, "Single-mode oscillation of laser-diode-pumped Nd:YVO4 microchip lasers", Opt. Lett. 16, 1955 (1991), CrossRef Z. Lin, C. Gao, M. Gao, Y. Zhang, H. Weber, "Diode-pumped single-frequency microchip CTH:YAG lasers using different pump spot diameters", Appl. Phys. B 94, 81 (2009). CrossRef V. Evtuhov, A.E. Siegman, "A “Twisted-Mode” Technique for Obtaining Axially Uniform Energy Density in a Laser Cavity", Appl. Opt. 4, 142 (1965), CrossRef P. Polynkin, A. Polynkin, M. Mansuripur, J. Moloney, N. Peyghambarian, "Single-frequency laser oscillator with watts-level output power at 1.5 µm by use of a twisted-mode technique", Opt. Lett. 30, 2745 (2005), CrossRef E. Wu, H. Pan, S. Zhang, H. Zeng, "High power single-longitudinal-mode operation in a twisted-mode-cavity laser with a c-cut Nd:GdVO4 crystal", Appl. Phys. B 80, 459 (2005). CrossRef M.V. Okhapkin, M.N. Skvortsov, A.M. Belkin, N.L. Kvashnin, S.N. Bagayev, "Tunable single-frequency diode-pumped Nd:YAG ring laser at 1064/532 nm for optical frequency standard applications", Opt. Comm. 203, 359 (2002), CrossRef T.J. Kane, R.L. Byer, "Monolithic, unidirectional single-mode Nd:YAG ring laser", Opt. Lett. 10, 65 (1985), CrossRef B. Yao, X. Duan, D. Fang, Y. Zhang, L. Ke, Y. Ju, Y. Wang, G. Zhao, "7.3uW of single-frequency output power at 2.09 μm from an Ho:YAG monolithic nonplanar ring laser", Opt. Lett. 33, 2161 (2008), CrossRef X. Zhang, Y. Ju, Y. Wang, "Diode-end-pumped room temperature Tm,Ho:YLF lasers", Opt. Expr. 13, 4056 (2005), CrossRef G.J. Friel, A.J. Kemp, T.K. Lake, B.D. Sinclair, "Compact and Efficient Nd:YVO 4 Laser that Generates a Tunable Single-Frequency Green Output", Appl. Opt. 39, 4333 (2000), CrossRef T.Y. Fan, "Single-axial mode, intracavity doubled Nd:YAG laser", IEEE J. Quantum Electron. 27, 2091 (1991). CrossRef H. Nagai, M. Kume, I. Ohta, H. Shimizu, M. Kazamura, "Low-noise operation of a diode-pumped intracavity-doubled Nd:YAG laser using a Brewster plate", IEEE J. Quantum Electron. 28, 1164 (1992). CrossRef C. Pedersen, P. Lichtenberg Hansen, T. Skettrup, P. Buchhave, "Diode-pumped single-frequency Nd:YVO4 laser with a set of coupled resonators", Opt. Lett. 20, 1389 (1995), CrossRef I. Häggström, B. Jacobsson, F. Laurell, "Monolithic Bragg-locked Nd:GdVO4 laser", Opt. Expr. 15, 11589 (2007), CrossRef J. Watanabe, T. Harimoto, "Oscillating longitudinal-mode control of a microchip green laser by injection current", Opt. Expr. 15, 965(2007), CrossRef Y. Ma, L. Wu, H. Wu, W. Chen, Y. Wang, S. Gu, "Single-longitudinal mode Nd:YVO4 microchip laser with orthogonal-polarization bidirectional traveling-waves mode", Opt. Expr. 16, 18702 (2008), CrossRef J.Z. Sotor, G. Dudzik, A.J. Antonczak, K.M. Abramski, "Single-longitudinal mode, monolithic, green solid-state laser", Appl. Phys. B 103, 67 (2010). CrossRef J.Z. Sotor, A.J. Antończak, K.M. Abramski, "Single-longitudinal mode Nd:YVO4/YVO4/KTP green solid state laser", Opto- Electron. Rev 18, 75 (2010). CrossRef J.Z. Sotor, G. Dudzik, K.M. Abramski, "Single frequency, monolithic Nd:YVO4/YVO4/KTP diode pumped solid state laser optimization by parasitic oscillations elimination", Opt. Comm. 291, 279 (2013), CrossRef J.Z. Sotor, G. Dudzik, G.J. Sobon, K. Krzempek, K.M. Abramski, "0.5W single-longitudinal mode, monolithic Nd:YVO4 microchip laser", in CLEO: 2013, OSA Technical Digest (online) (Optical Society of America, 2013), paper CTh4I.7, CrossRef